Autocratic legalism in the perspective of the role of judges in societies of new democracies - Kaczmarek, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The advent of autocratic legalism prompts the presentation of the role of judges in societies of new democracies. The recommended proposal modifies the vision of judges as guardians of the law with an educational-democratic component, in which judges also become interpreters of the law. This article offers a presentation of this proposal. It will commence in two stages. The first is a reconstructive and interpretative process. Its aim is to present autocratic legalism and then, in its light, the problem of the abusive judicial review. The second one is of a normative nature, i.e. a presentation of the social role of judges. In this proposal, judges can be assigned three moral obligations: a) to protect the democratic system, b) to improve legal standards and public institutions when they are dysfunctional, and c) to educate the citizenry, with a particular emphasis on human rights. A primary argument in favour of such a role for judges is the strengthening of civil society as an important safeguard against autocratic rule. The context for the findings presented in this paper is the current constitutional crisis in the Polish legal order. However, empirical documentation does not determine the research methodology in the presented article. In it, I pursue an approach that can be described as “doing philosophy historically.”
Keywords: autocratic legalism; abusive judicial review; the role of judges; liberal democracy